Interaction of hydrogen with the microstructure of low-carbon steel - Ramunni, Viviana Patricia (2006)
The interaction of hydrogen (H) with the microstructure of SAE 1008 type low-carbon steel is studied in this work. The objective is to determine the binding energy of H with the cementite (Fe3C) for three different conditions of the carbide. Electrochemical permeation tests are combined with the numerical resolution of Fick´s equations assuming that hydrogen is delayed during de transport by reversible trapping sites. Techniques of H vacuum desorption are also employed to describe irreversible trapping. From permeation tests, we obtain the density of reversible trapping sites and the probabilities of H capture and release from which the binding energy is evaluated. From effusion test, weak and strong trapping sites with energies in the range of 10-50 kJ/mol H were observed.